Can Companies Make Green Innovation a Reality by Means of Corporate Environmental Responsibility? The Mediating Role of Environmental Subsidies - Yu, Li Shi; Xiangyuan, Ao; San, Ong Tze; Anqi, Chen; Mengdie, Zhang (International Journal of Energy Economics and Policy, 2022)
This paper analyses how Chinese listed companies have channelled their environmental responsibility through government resources by observing corporate behaviour between 2015 and 2020. Results indicate that corporate environmental responsibility does not directly enhance corporate green innovation (CGI) and that government environmental subsidies (ES) are required to positively incentivise CGI capabilities. Increased corporate investment in environmental protection and improved governance are positive for CGI, unlike environmental management system certification. This paper provides novel ideas for future research on how Chinese listed companies may convert their environmental responsibility into green innovation through government ES. This may benefit future research on sustainable development.